Investigating the effectiveness of virtual education in the field of learning interaction and evaluation from the point of view of dental students of Babol University of Medical Sciences in 2020-2021 based on Crickpatrick\'s model. - Maryam Ghaemi Amiri; Sber Zaebjani; Mohammad Mehdi Naghibi Sistani (Babol University of Medical Sciences, 2023)
Objective: Nowadays, due to the expansion of the use of online technologies in the education of students, it is important to evaluate the effectiveness of these educations in evaluating and ensuring the academic progress of students. Crickpatrick's model is a very efficient tool for educational evaluation. The aim of this research is to investigate the effectiveness of virtual education in the field of learning and evaluation based on the first level of this model Method: This descriptive cross-sectional study was conducted on 140 dental students. Students answered a researcher-made questionnaire about the effectiveness of virtual education. CVR (Content Validity Ratio) indices were used to confirm the validity and quantification of experts' opinions and CVI (Content Validity Index) indices were used to confirm the ability to implement the questionnaire. Cronbach's alpha calculation was used to confirm the reliability of the questionnaire and the Test-Retest method was used to check the repeatability of this questionnaire. Finally, the data obtained from the questionnaire was entered into SPSS V.20 software and the data was evaluated with the help of independent t-test and one-way analysis of variance so that P < 0.05 was considered significant. Findings: The average age of the students was 23.45 years with a total average of 15.94. In general, students reported an average of 50% of the effectiveness of virtual education on learning. Effectiveness was declared in the field of evaluation by 51% and in the field of learning interaction by 49%. In general, demographic characteristics did not have a significant effect on the effectiveness of virtual education from their point of view (p<0.05) Conclusion: Considering that the level of effectiveness of virtual education on the learning of dental students of Babol University of Medical Sciences was reported as average, it seems that in order to improve the interaction in learning and evaluation of students, there is a need to increase the quality of presenting lessons, planning, test content and using tools and facilities. Education is suitable